Dynamics of Toxorhynchites splendens population in the Larval phase at a rubber plantation in Banjarbaru, South Kalimantan, Indonesia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Muhamat, Hadisusanto S, Umniyati SR, Soesilohadi RCH. 2021. Dynamics of Toxorhynchites splendens population in the Larval phase at a rubber plantation in Banjarbaru, South Kalimantan, Indonesia. Biodiversitas 22: 4915-4922. This study aims to describe a water-filled rubber sap bowl as a habitat for larval Toxorhynchites splendens. The research used a quota drive count method, taking the first 10 rubber sap bowls found in the study area: (i) with larval Tx. splendens, (ii) with other mosquito larvae, (iii) with water but without mosquito larvae, and (iv) without water. The number of larval Tx. splendens was calculated based on the developmental phase and other mosquito larvae present in each bowl. Environmental factors, such as temperature and humidity, rainfall, wind velocity, and duration of irradiation were the additional data. The results of this study showed that the average frequency of On average, over 20% of bowls contained larval Tx. splendens, and the percentage increased in high rainfall. During low rainfall in August and September, Tx. splendens used water-filled rubber sap bowls as breeding places. This study concludes that Tx. splendens can make use of water-filled rubber sap bowls as places for breeding. Each rubber sap bowl contained one or more individuals of instar larvae 2, and the number decreased as the developmental phase continued because of the limited volume of water in the bowl, cannibalism, and the number of other mosquito larvae as prey.
Keywords: cannibalism, immature Tx. splendens, latex sap bowl, predator, rainfall